Internet of Things-Based Hidroponic Plant Monitoring System - Hasanah, Herliyani; Susanto, Rudi; Lestari, Wiji (ISB Atma Luhur, 2025)
Hydroponic farming is gaining popularity in urban areas due to its efficient use of space. However, this system requires careful management of nutrients, temperature, and pH, which are vital for plant growth but complex to manage manually. This study's purpose is to enhance hydroponic management, temperature, and pH. The study uses a Node MCU ESP8266 microcontroller and sensors to collect data, and the system is integrated with Telegram for easy monitoring. The prototyping methodology used in this study includes stages from analysis to testing and implementation. Test results show that the system accurately blends and adjusts pH and nutrient levels, and is compared to digital measuring instruments. This IoT-based, efficient solution for urban farmers and hydroponic practitioners significantly improves their ability to manage nutrient and environmental conditions, enabling more innovative, sustainable urban farming practices.